Strategies Use and Self-efficacy perceptions: Libyan EFL University Students - Alashouri, Rahma (Journal of English Language Teaching and Applied Linguistics, 2023)
Language learning strategies (LLSs) and the elements that affect their usage, like Self-efficacy (SE) and gender variations during the learning process, both of which have been significant areas of focus in the teaching of English as a foreign language (EFL) to students of other languages, as they play a pivotal role in the learning process. in the Libyan context research on this topic is relatively scarce. As a result, this study was conducted to determine if there is a link between LLS and SE; in order to accomplish this goal, this research surveyed 60 students who enrolled at the University of Tripoli (33 males and 27 females). Both SILL and the QESE were used in the process of data collection. To analyze the data, the software of (SPSS) was used to examine the data gathered. It was concluded that students’ utilization of LLSs was at a moderate level, with a noticeable gender difference; although students reported high levels of self-efficacy, a weak positive association across LLSs and SE was reported. The conclusion of the research shall be valuable to both researchers and teachers, as the study will provide ways to better understand students’ current views and strategy utilization.